Observations about the mucuna - corn system in the slopes of Waslala, Atlantic Region of Nicaragua. - Philipp, Dirk (2003)
A velvetbean-corn system utilized in hillside farming in Waslala,Nicaragua, was described and analyzed regarding farmer.sapproaches to conservational practices in agriculture. Datasuggested that the fresh biomass yield for velvet bean rangedfrom 11.4 to 60 t/ha, while the corn yield varied from 1.1 to5.4 t/ha. Apparently, the economic efficiency of the velvetbean-corn system depended on the origin of the velvet beanseeds and at what level additional labor was employed. Dataindicated that farmers who used own velvet bean seedsincreased their gross income by $185.80/ha. Additionally,when only family labor was employed, the gross incomeincreased by $265.11/ha compared to farmers who utilizedhired labor and obtained bean seeds off-farm. Suggestions onhow the described system may be improved regarding itssustainability are included by the authors.